Co-producing video performances across the Black Atlantic : an approach to participatory research-creation - Gruber, Valerie (2022)
Logocentric approaches to knowledge production can hardly address traumatic experiences such as the transatlantic trade in enslaved Africans. Video performances are a fruitful way to explore and exchange such embodied knowledges and collective memories, passing them on to future generations. This presentation gives insight into a participatory research-creation process developed with Afro-diasporic artists and community actors from Brazil, Colombia and Mozambique. We will show fragments of transdisciplinary video performances produced during the Covid-19 pandemic. They provide a means for personal and collective reflection and transcontinental collaboration at the intersection of artistic research and socially engaged art. This approach offers an important opportunity to connect diverse actors from both shores of “The Black Atlantic” (Gilroy, 1993). We will discuss the shifting roles between academic researchers and co-creators of knowledge from different socio-spatial contexts and artistic fields such as music, dance and poetry. Thereby, we will gauge the possibilities and limitations of transformation emerging from a co-creation of artistic/academic knowledges based on communal practices, joint reflections and mutual learning.